Bypass grafting to the third segment of the vertebral artery for symptomatic extensive vertebrobasilar atherosclerotic disease - Quentin Pellenc, MD, PhD; Régis Renard, MD; Augustin Gaudemer, MD; Pierre Amarenco, MD; Philippa Lavallée, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
Symptomatic vertebrobasilar atherosclerotic disease is rarely encountered but represents a high-risk factor for recurrent transient ischemic attack or stroke. Posterior strokes are usually associated with embolism or hemodynamic impairment. Extensive disease involving the V3 and V4 segments of the vertebral artery (VA) remains infrequent, and optimal management is limited owing to the infrequency of this disease. We illustrate the case of a 65-year-old man who presented with recurrent transient episodes of dizziness with acute onset of instability, nausea, and left visual blurring. Magnetic resonance imaging findings of the head were normal, and computed tomography angiography revealed severe atherosclerotic disease of both VAs, with proximal occlusion of the right VA and multiple tight stenoses of the left VA at the V1 and V4 segments. Duplex ultrasound found markedly reduced anterograde flow in the VAs and basilar arteries and nonsignificant stenosis of the internal carotid arteries. Optimal medical treatment led to a decrease of transient symptoms. However, the patient developed a cerebellar infarction in the left posteroinferior cerebellar artery territory with left VA V4 segment occlusion. Surgical revascularization of the right VA was decided by the multidisciplinary team. Through an anterolateral approach of the right VA V3 segment, revascularization was performed using a common carotid artery-to-right VA bypass using a reversed saphenous vein graft. The patient fully recovered and was free of symptoms during the next 14 months of follow-up. In the case of extensive VA occlusive disease, surgical reconstruction of the distal VA using a bypass from the common carotid artery represents an option to improve hemodynamics and/or eliminate an embolic source of posterior stroke on a case-by-case basis.